Identity, religion and empire: the civic coins of Roman Phoenicia - Webster, Olivia (2019)
This thesis will examine the role that religious imagery on civic coinage played in the expression of identities and religious mentality in Roman Phoenicia. This medium comprised low-value bronze currency, which was produced by individual cities for primarily local use. Their reverses preserve a vast corpus of imagery but, despite this repository of visual evidence, there are only a few studies that engage with the material and none that focus solely on Phoenicia. When working with numismatic evidence there has been a tendency either to accept the images shown as completely realistic, or to reject the informative potential of designs outright. This approach aims to seek a middle ground between these extremes: to accept the limitations and challenges of numismatic material, but also to demonstrate its validity as a resource.